Probing the speed of scalar induced gravitational waves from observations - Jun Li; Guang-Hai Guo; Yongcan Zu (European Physical Journal C: Particles and Fields)
Abstract The propagation speed of gravitational waves is a fundamental issue in gravitational theory. According to general relativity, gravitational waves propagate at the speed of light. However, alternative theories of gravity propose modifications to general relativity, including variations in the speed of gravitational waves. In this paper, we investigate scalar-induced gravitational waves that propagate at speeds different from the speed of light. First, we analytically calculate the power spectrum of scalar induced gravitational waves based on the speed and spectrum of primordial curvature perturbations. We then explore several scalar power spectra, deriving corresponding fractional energy densities, including monochromatic spectrum, scale-invariant spectrum, and power-law spectrum. Finally, we constrain scalar-induced gravitational waves and evaluate the signatures of their speed from the combination of CMB+BAO and gravitational wave observations. Our numerical results clearly illustrate the influence of the speed of scalar-induced gravitational waves.